Perencanaan Persediaan Bahan Baku dan Evaluasi Supplier Studi Kasus di PT. Romi Violeta - Syafi Ul Nur Wahid; Siti Mundari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT. Romi Violeta is an export furniture manufacturing company in Buduran, Sidoarjo, which faces the problem of inconsistency in mindi wood inventory due to fluctuations in demand for superior products. This condition causes stockouts, disrupts the production process, and hinders shipments. Another problem shows the unstable performance of 12 active suppliers. This study aims to determine optimal inventory planning and select the best suppliers using the Silver Meal Heuristic, Safety Stock, Reorder Point (ROP), and Analytical Hierarchy Process (AHP) methods. The results of the study showed that the Silver Meal method produced 9 optimal order cycles with a total inventory cost of IDR 3,908,169, more economical than IDR 234,303 compared to actual conditions and was able to eliminate 5 stockout incidents. The value of Safety Stock is 784 pcs and ROP is 1,697 pcs. Based on AHP, the reject rate is the main criterion, and CV. AP was selected as the best supplier with a global priority value of 0.1220.